Plasmid-encoded gene duplications of extended-spectrum β-lactamases in clinical bacterial isolates - Sobkowiak, Annika; Scherff, Natalie; Schuler, Franziska; Bletz, Stefan; Mellmann, Alexander; Schwierzeck, Vera; van Almsick, Vincent (Frontiers in Cellular and Infection Microbiology, 2024)
The emergence of extended spectrum β-lactamase (ESBL)-producing Enterobacteriaceae is an urgent and alarming One Health problem. This study aimed to investigate duplications of plasmid encoded ESBL genes and their impact on antimicrobial resistance (AMR) phenotypes in clinical and screening isolates.Methods: Multi-drug resistant bacteria from hospitalized patients were collected during routine clinical surveillance from January 2022 to June 2023 and their antimicrobial susceptibility patterns were determined. Genotypes were extracted from long-read whole genome sequencing data. Furthermore, plasmids and other mobile genetic elements associated with ESBL genes were characterized and the ESBL genes were correlated to ceftazidime minimal inhibitory concentration (MIC).In total, we identified four cases of plasmid-encoded ESBL gene duplications that match four genetically similar plasmids during the 18-months surveillance period: Five Escherichia coli and three Klebsiella pneumoniae isolates. As the ESBL genes were part of transposable elements, the surrounding sequence regions were duplicated as well. In-depth analysis revealed insertion sequence (IS) mediated transposition mechanisms. Isolates with duplicated ESBL genes exhibited a higher MIC for ceftazidime in comparison to isolates with a single gene copy (3 ->256 vs. 1.5 -32 mg/L, respectively).ESBL gene duplications led to an increased phenotypic resistance against ceftazidime. Our data suggests that ESBL gene duplications by an IS-mediated transposition is a relevant mechanism how AMR develops in the clinical setting and is part of the microevolution of plasmids.